Time-Domain Modeling of a Distribution System to Predict Harmonic Interaction Between PV Converters - Grazia Todeschini (IEEE Transactions on Sustainable Energy, 2019)
Due to the interaction converter control, pre-existing distortion and grid impedance, the harmonic levels caused by renewable energy sources (RESs) are continuously changing, and their assessment requires the use of dedicated computer models. Several time-domain models have been proposed to carry out this analysis, however, they fall short of at least one requirement: either they do not provide accurate results, or they require an excessively long simulation time. This paper presents a novel time-domain model to address the gap described above: the proposed model employs average functions and a novel switching emulator. Therefore, it is referred to as ‘average model with switching emulator’ (AMSE). The proposed model is compared with existing models, and the results indicate that the AMSE meet both requirements stated above, as it accurately represents harmonic distortion while reducing significantly the simulation time. The second part of the paper discusses mitigating solutions to harmonic amplification in systems with a high penetration of VSCs, and shows the effectiveness of using an Active Filter to reduce harmonic levels in system experiencing resonance conditions.